Tipicidad en blanco y garantías constitucionales : a propósito de la sentencia de la Corte Suprema de Justicia, Sala de Casación Penal, Rad. 40089 del 5 de octubre de 2016. M.P. José Francisco Acuña Vizcaya : aprobado acta no. 312 (2017)
The criminal law expansion phenomenon in Colombia has led to appear or sometimes remain in our legal system, behaviors typified as crimes that do not meet the minimum theoretical assumptions that grant them legitimacy. In this way, it is stated that criminal law, in general, and the principle of legality, in particular, are in crisis. As part of the doctrine points out, there is a continuous loss of importance of the law, as well as of the limitless expansion of criminal law in the punitive field, through normative statements that do not respect the implicit mandates of the principle of legality. In the midst of this context is framed the discussion that gives rise to the sentence of October 5, 2016 of the Supreme Court of Justice. In this case, the Criminal Cassation Chamber discusses the problematic that revolves around the interpretation of the scope of blank criminal types, to determine the type of criminal conduct of illegal destination of fuel contained in art. 327D of the Penal Code.